Comparison of Concomitant Mesalamine and Immunomodulator Therapy and Immunomodulator Monotherapy for Crohn’s Disease - Min Seob Kwak; Kyung-Jo Kim; Jae Hee Cheon; Wan Soo Kim; Jeong-Mi Lee; Sung Wook Hwang; Sang Hyoung Park; Dong-Hoon Yang; Byong Duk Ye; Jeong-Sik Byeon; Seung-Jae Myung; Suk-Kyun Yang (Gastroenterology Research and Practice)
Background. Although immunomodulators are increasingly used in Crohn’s disease (CD), a significant number of gastroenterologists still use 5-aminosalicylate (5-ASA) in combination with azathioprine (AZA) or 6-mercaptopurine (6-MP); there is limited evidence regarding the benefit of concomitant 5-ASA with AZA/6-MP compared with AZA/6-MP monotherapy for the treatment of CD. Study Design. A total of 106 patients who received AZA/6-MP for more than 3 months between January 1991 and May 2014 were identified retrospectively. Each patient was matched with 3 randomly selected controls who were treated with concomitant therapy during the same period. Results. The cumulative probabilities of steroid use at 5 and 10 years were 24.9% and 75.8% in the 5-ASA + AZA/6-MP group and 31.2% and 87.8% in the AZA/6-MP group, respectively (P=0.187). The cumulative probabilities of anti-TNF use, resectional surgery, and disease-related hospitalization were comparable between the groups. The younger age and the use of lower doses of immunomodulators were associated with higher requirement of rescue therapy. Conclusions. This study did not demonstrate that the concomitant use of 5-ASA with AZA/6-MP showed the proof or effect in terms of steroid requirements, anti-TNF use, resectional surgery, or disease-related hospitalization compared with that of AZA/6-MP alone.